Hydrogeochemistry and Quality Assessment of Shallow Groundwater in the Southern Part of the Yellow River Alluvial Plain (Zhongwei Section), Northwest China - Peiyue Li (Earth Sciences Research Journal, 2014)
Statistical analyses, a Piper diagram, the saturation index and the correlations of chemical parameters were used to reveal the hydrogeochemistry and hydrogeochemical evolution of shallow groundwater in the southern part of the Zhongwei section of the Yellow River alluvial plain. The water quality for agricultural and domestic uses was also assessed in the study. The results suggest that the shallow groundwater in the study area is fresh to moderately mineralized water. Higher Ca2+ and HCO3- are observed in the less mineralized water, whereas Na+ and SO42- are common ions in the highly mineralized water. The major hydrochemical facies for groundwater with total dissolved solids (TDS) <1 g/L are HCO3-Ca·Mg and HCO3-Ca·Na·Mg, and for groundwater with TDS > 1 g/L, SO4 ·Cl-Na and SO4·Cl-Na·Mg·Ca are the predominant hydrochemical types. The main reactions in the groundwater system are the dissolution/precipitation of gypsum, fluorite, halite, calcite and dolomite. Cation exchange is also important in controlling the groundwater chemistry. The water samples assessed in the paper are of acceptable quality for agricultural use, but most of them are not fit for direct human consumption (drinking). TDS, total hardness (TH), Cl- and SO42- are the main indices that result in the poor drinking water quality.